Effect of teaching games for understanding approach on students' cognitive learning outcome - Balakrishnan, M.; Rengasamy, S.; Aman, M.S. (2011)
The study investigated the effects of Teaching Games for Understanding approach on students' cognitive learning outcome. The study was a quasi-experimental non-equivalent pretest posttest control group design whereby 10 year old primary school students (n=72) were randomly assigned to an experimental and a control group. The experimental group students were exposed with TGfU approach and the control group with the Traditional Skill approach of handball game. Game Performance Assessment Instrument (GPAI) was used to measure students' tactical understanding and decision making in 3 versus 3 handball game situations. Analysis of covariance (ANCOVA) was used to analyze the data. The results reveal that there was a significant difference between the TGfU approach group and the traditional skill approach group students on post test score (F (1, 69) = 248.83, p < .05). The findings of this study suggested the importance of TGfU approach to improve primary students